Enantioselective Organocatalyzed Functionalization of Tetramic and Tetronic Acids. Issue 22 (26th October 2022) - Ciber, Luka; Gorenc, Ana; Hozjan, Mišel; Požgan, Franc; Svete, Jurij; Brodnik, Helena; Štefane, Bogdan; Grošelj, Uroš
Abstract: Organocatalyzed Michael addition of N‐substituted tetramic acids to nitroalkene acceptors followed by O ‐alkylation gave polyfunctionalized tetramic acid (31 examples, 59–94% ee ). The enantioselectivity of the product was influenced by the N‐substituent of the substrate. Quantum chemical methods provided the mechanistic insights of the studied transformation. The preferred reaction pathway follows the model proposed by Pápai et al. Single crystal structure confirmed the absolute configuration, which was in line with the ECD measured and calculated structure. Additionally, a comparative study of the alkylation of a selected tetramic and tetronic acid with trans ‐β‐nitrostyrene is disclosed. Follow‐up amidations demonstrated the applicability of this class of compounds for the incorporation into both dipeptide and depsipeptide sequences. Abstract :